Textile waste management strategies in the Metropolitan Region of Stockholm - Marchi, Cristina Maria Dacach Fernandez (Pontifícia Universidade Católica de São Paulo, 2019)
The fashion industry produces more than the population needs, which leads to water depletion and generation of waste and pollution. It is considered that the textile reuse activity requires civic behaviour, adequate infrastructure and innovative business models. This study aimed to describe the structural characteristics of the management of textile disposal and reuse in order to show the practices that sustain the trade of second-hand products in the Metropolitan Region of Stockholm, Sweden. The methodology used was the descriptive and exploratory multiple case study. Results indicate that the facilities in handling textile waste for collection, sorting and distribution and the policies adopted by Sweden favor the growth of sustainable businesses connected with this production chain.